2014
DOI: 10.1007/s12070-014-0754-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of H. Pylori in Tonsillar Tissue of Patients with Chronic Recurrent Tonsillitis Using Rapid Urease Test in a Tertiary Referral Hospital in Sub Saharan Africa

Abstract: There has been conflicting results regarding the presence of H. pylori in tonsillar tissue. Our objective was to analyze for the presence of H. pylori in tonsillar tissue in patients undergoing tonsillectomy for chronic recurrent tonsillitis using rapid urease test in a Tertiary care academic medical center in a sub Saharan hospital. A prospective cross-sectional analysis of 39 consecutive cases of patients undergoing tonsillectomy secondary to chronic recurrent tonsilitis was done. Rapid urease test was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…This will lead to accumulation of ammonium ion. This will then cause a rise in the pH and this is detected in the pH indicators by a colour change in the system from yellow to pink or red [7].…”
Section: Rapid Urease Testmentioning
confidence: 99%
“…This will lead to accumulation of ammonium ion. This will then cause a rise in the pH and this is detected in the pH indicators by a colour change in the system from yellow to pink or red [7].…”
Section: Rapid Urease Testmentioning
confidence: 99%
“…12 Using a rapid urease test, another report showed that H. pylori was present in 30.5% of the tonsillar tissue of patients with chronic recurrent tonsillitis. 13 The deleterious effects of environmental tobacco smoke (ETS) exposure on the upper respiratory tract of children are becoming increasingly recognized. A previous study showed that there was a significant association between children's sore throats and maternal smoking.…”
Section: 11mentioning
confidence: 99%
“…Direct and/or indirect mechanisms were involved in association between Hp and upper respiratory tract diseases, various studies over the past two decades have suggested such relationship [13] , where Saki et al [14] detected heavy colonization of HP in adenoid tissue and middle ear, Nártová et al [15] and Ochung'o et al [16] also detected HP in tonsil specimens after tonsillectomy for chronic tonsillitis and sleep apnea syndrome patients.…”
Section: Introductionmentioning
confidence: 99%